An amino acid change in nsP4 of chikungunya virus confers fitness advantage in human cell lines rather than in Aedes albopictus. (15th October 2019) - Fu, Jolene Yin Ling; Chua, Chong Long; Vythilingam, Indra; Sulaiman, Wan Yusoff Wan; Wong, Hui Vern; Chan, Yoke Fun; Sam, I-Ching
Abstract : Chikungunya virus (CHIKV) has caused large-scale epidemics of fever, rash and arthritis since 2004. This unprecedented re-emergence has been associated with mutations in genes encoding structural envelope proteins, providing increased fitness in the secondary vector Aedes albopictus . In the 2008–2013 CHIKV outbreaks across Southeast Asia, an R82S mutation in non-structural protein 4 (nsP4) emerged early in Malaysia or Singapore and quickly became predominant. To determine whether this nsP4-R82S mutation provides a selective advantage in host cells, which may have contributed to the epidemic, the fitness of infectious clone-derived CHIKV with wild-type nsP4-82R and mutant nsP4-82S were compared in Ae. albopictus and human cell lines. Viral infectivity, dissemination and transmission in Ae. albopictus were not affected by the mutation when the two variants were tested separately. In competition, the nsP4-82R variant showed an advantage over nsP4-82S in dissemination to the salivary glands, but only in late infection (10 days). In human rhabdomyosarcoma (RD) and embryonic kidney (HEK-293T) cell lines coinfected at a 1 : 1 ratio, wild-type nsP4-82R virus was rapidly outcompeted by nsP4-82S virus as early as one passage (3 days). In conclusion, the nsP4-R82S mutation provides a greater selective advantage in human cells than in Ae. albopictus, which may explain its apparent natural selection during CHIKV spread in Southeast Asia. This is an unusual example of a naturally occurring mutation in a non-structural protein, which may have facilitated epidemic transmission of CHIKV.